Innovation dynamics and financial stability: a European Union perspective - Santos-Arteaga, Francisco Javier; Tavana, Madjid; Torrecillas, Celia; Di Caprio, Debora (Technological and Economic Development of Economy, 2020)
We present a formal and empirical framework that links the technological capacity of a country, reflected in its National System of Innovation, with the financial constraints it faces. The paper is divided into two sections. The first one introduces a stochastic growth model based on the relative level of technological development of countries, which determines their productivity and capacity to finance innovation activities. The second section describes the empirical conditioning observed in the innovation outputs of countries determined by their financial constraints and time period relative to the economic crisis of 2008. We classify a panel sample of European Union countries according to their technological development level and find that financial stability constraints negatively affect the less developed ones, a relationship that weakens as their innovation capacity increases. We also observe that financial stability becomes significant among technologically developed countries when reacting to the exogenous shock triggered by the crisis, while laggards remain constrained through the entire 2000–2018 sample period.